PROFIL TINGGI BADAN ANAK USIA BARU MASUK SEKOLAH (TBABS) DI BEBERAPA KABUPATEN/KOTA DI INDONESIA: Analisis Data Riskesdas 2007 - Hermina Hermina; Sri Muljati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2010)
Background: One of nutrition indicator is determined by good quality of human resource reflected by anthropometry such as body height. Objectives: The aim of th1s analysis is to measure the height of pre-elementary school children in rural and urban Indonesia. Methods: Data source of this analysis is Riskesdas Data (2007). Analytic unit of this study was house hold who had new prelimenary school children. (6-7 years old). Variable which was anthropometry data, height for age and sex, was analysed using software anthropometry plus WHO 2007 as standard reference. Other variables were social economic, head of family's job, living place (rural or urban) and income expenditure per-capita (kuintil). Results: This result shows that prevalence of pre-elementary school children having stunted is 28.4%. Whereas having normal height standard (WHO 2007) is 90.4%. There is no significant difference between boys and girls' height. However, children's height in rural and urban are different signicantly. More short pre-elementary students are found in rural than urban area. No significant relationship is found beetwen house hold social economic status and children's height. Conclusions: Prevalence of pre-elementary school children having stunted is 28.4%. More short pre-elementary students are found in rural than urban area.  Keywords: height, stunted, pre-elementary school children, social-economic, rural-urban